Chemical Compositions and Nutrient Degradation of Elephant Grass Silage Ensiled with Black Tea Waste - Santoso, B; Lekitoo, MN; Umiyati, Umiyati (ANIMAL PRODUCTION, 2007)
This study evaluated the chemical compositions and nutrient degradation during ensiling of elephant grass (Pennisetum purpureum) silage with black tea waste (BTW) addition.  Four silage treatments were elephant grass (S0); elephant grass + 100 g BTW/ kg fresh matter (S1); elephant grass + 200 g BTW/kg fresh matter (S2); elephant grass + 300 g BTW/kg fresh matter.  About 220 g of silage material were ensiled for 30 days at room temperature (approximately 28°C).  Three replicates were prepared for each treatment.  Results showed that dry matter, organic matter and crude protein contents of silages increased linearly (P<0.01) with increasing black tea waste.  There were linear decreases in dry matter and crude protein degradations (P<0.01) and organic matter degradation (P<0.05) during ensiling with increased black tea waste addition.  Dry matter degradation values varied from 15.03 to 30.71% and were higher than degradation value of ideal silage.  It was concluded that black tea waste has potential as a silage additive to improve nutritive value and fermentation quality of elephant grass silage.  (Animal Production 9(2): 160-165 (2007)  Key Words: Elephant grass, black tea waste, silage additive, degradation